Application Of Data Mining Techniques In Higher Education In India - Ranjan, Jayanthi; Ranjan, Raju (Journal of Knowledge Management Practice, 2010)
In last decade, the higher education in India has grown manifolds. Private participation in establishing new institutions, encouraged by the government forced the higher education to revisit their scope and objectives in the long run to sustain. The regulatory bodies, though, have framed guidelines for various infrastructures, faculty and other resources but in many cases this has been grossly violated leading to inferior education further culminating into un-employability of the students. The paper aims to purpose the use of data mining techniques to improve the efficiency of higher educational institutions. If data mining techniques such as clustering, decision tree, association can be applied to higher education processes, it can help improve students’ performance, their life cycle management, selection of course and major, their retention rate and grant/fund management of an institution. This is the first approach to examine the effect of using data mining techniques in higher educational institutions in Indian perspective.
Keywords: knowledge management; Data mining; Higher education; Clustering; Decision tree; Neural network; Genetic algorithm